Hodnocení klinického stadia a léčebné odpovědi u maligních lymfomů - doporučení Kooperativní lymfomové skupiny na základě revidovaných kritérií z roku 2014 (Luganská klasifikace) - Sýkorová, A; Pytlík, R; Móciková, H; Belada, D; Benešová, K; Papajík, T; Janíková, A; Šálek, D; Procházka, V; Vokurka, S; Campr, V; Klener, P; et al. (Klinicka onkologie, 2016)
BACKGROUND: Recent advances in the use of the imaging modalities, especially PET/CT, and their utilization for determining clinical stage (CS) and assessment treatment response (TR) in malignant lymphomas, along with development of prognostic tools and new treatment modalities, formed the basis for the revised criteria for evaluating CS and TR (published as the Lugano classification, 2014). MATERIALS AND METHODS: The authors summarize the new Lugano recommendations (published in 2014) and the changes from the criteria published in 2007. Moreover, discussion of the changes places emphasis on practical use. The practicality of the Lugano classification, 2014 was the subject of consensus meeting at the annual meeting of the Cooperative Lymphoma Study Group (CLSG) in March 2015. This study reports the final consensus. The CLSG recommends use of the Lugano classification, 2014, but recommends some modifications. CONCLUSIONS: Standardization of the criteria used to determine CS and TR in malignant lymphomas has led to improvements in initial staging and assessment of TR. The criteria are helpful for unifying response assessment in clinical trials and simplify the work of regulatory agencies (e.g., the EMA and the Czech State Institute for Drug Control) when registering new drugs. It also allows evaluation of treatment outcomes outside clinical trials, for example within the CLSG prospective registry of patients with newly diagnosed lymphoma. KEY WORDS: malignant lymphoma - computed tomography - positron emission tomography - staging - treatment responseThis work was supported by the grant Prvouk P27/2012 of the Third Faculty of Medicine, Charles University in Prague and by the grant of the Czech Lymphoma Study Group No. NT12193-5/2011.The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 24. 1. 2016Accepted: 16. 2. 2016.
Keywords: směrnice pro lékařskou praxi jako téma; Positron Emission Tomography Computed Tomography; Neoplasm Staging; Disease Management; staging nádorů; Lymphoma; lymfom; Practice Guidelines as Topic; Humans; management nemoci; Czech Republic; PET/CT; lidé; Česká republika